Pentingnya Pendidikan Karakter Pada Anak Sekolah Dasar Sebagai Implementasi Pendidikan Pancasila Dan Kewarganegaraan - Ayu Syarifah Lestari; Cindy Putri Widyawati; Ferdinan Tegar Wicaksono; Nela Rofisian (CV. ITTC INDONESIA, 2024)
Character education is an important aspect in children's development, especially at the elementary school (SD) level, which plays a fundamental role in shaping students' personality and morality from an early age. Character education aims to build positive attitudes and values, such as honesty, discipline, responsibility, and tolerance needed in social life. The implementation of character education through Citizenship Education (PKn) at the elementary school level is very relevant, considering that Civics focuses on instilling moral, social and nationalist values. The implementation methods used include integrating character material in the curriculum, contextual approaches that are relevant to the student's environment, and extracurricular activities that support the formation of positive character. The results of this study show the effectiveness of character education implemented through Civics in increasing students' understanding of moral and ethical values, as well as strengthening social relationships between students. Thus, character education in elementary schools as a form of implementation of Civics not only provides a scientific basis, but also shapes students into individuals with integrity and social sensitivity.